The Effect of Social Isolation on the Mental Health of Families of COVID-19 Patients in Kupang City - Nalle, Yabes Nindy Elicia; Syamruth, Yendris K. (Timorese Journal of Public Health, 2025)
The COVID-19 pandemic has caused stress at various levels of society. Concern and fear of this virus triggers a negative stigma, especially towards infected individuals, including the families of patients who died from COVID-19. This stigma can have a significant impact on the mental health of the family left behind. This study aims to analyze the effect of social exclusion on the mental health of families of COVID-19 patients who died in Kupang City. This study used a quantitative method with a cross-sectional design and involved 95 respondents. Data were collected using questionnaires and analyzed by simple linear regression. The results of this study show that social exclusion has a significant influence on the mental health of families of COVID-19 victims in Kupang. Based on simple linear regression analysis, a determination coefficient (R²) of 0.310 was obtained, which means that social exclusion contributed 31.0% in influencing mental health. Meanwhile, the remaining 69.0% were influenced by other factors not examined in the study, such as economic factors, social support, and the individual's psychological condition before experiencing social exclusion. Thus, this study confirms that social exclusion is a factor that affects the mental health of the families of COVID-19 patients who died. Therefore, more attention is needed from various parties to support individuals who experience social exclusion in order to maintain their mental well-being.